SINTESIS NANOPARTIKEL SERAT RAMI DENGAN METODE ULTRASONIKASI UNTUK APLIKASI FILLER BIONANOKOMPOSIT - D Kurniawan (Jurnal Biofisika, 2012)
Synthesis  of  nanoparticles  was  obtained  from  the  hemp  fiber  ultrasonic  method. Nanoparticles hemp fiber is used as  bio-nanocoomposite Ultrasonic method of hemp fiber was done with  the time variations  of surfactant tween 80 3  % as many as 10 samples and 0 % as much as 3 samples. All samples were tested with the Particle Size Analyzer (PSA) to determine the size distribution. The smallest sized fiber  was obtained from 105 min sonication with 3 % tween 80, the size is  229.04  nm.  Hemp fiber  size  with  concentration  of  tween  80  3  %  smaller  than  the  concentration  of Tween 80 0 %. Hemp fibers with nanometer-  size 229.04 has a density of 1.1727 g cm -  3 is smaller than 7500 nanometers in size hemp fibers with a density of 1.7083 g cm -  3 . Results of X -  ray Diffraction ( XRD ) showed the smallest size hemp fiber hemp is a cellulose fiber , characterized by their crystal phase cellulose is at 22.76 degrees diffraction angle with the degree of crystallinity 21.3727 %